2016
DOI: 10.1038/bjc.2016.398
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers in anal cancer: from biological understanding to stratified treatment

Abstract: Squamous cell carcinomas of the anus and anal canal represent a model of a cancer and perhaps the first where level 1 evidence supported primary chemoradiotherapy (CRT) in treating locoregional disease with curative intent. The majority of tumours are associated with infection with oncogenic subtypes of human papilloma virus and this plays a significant role in their sensitivity to treatment. However, not all tumours are cured with CRT and there remain opportunities to improve outcomes in terms of oncological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 53 publications
0
37
1
Order By: Relevance
“…Lymph node metastases have previously been shown to be a significant prognostic factor 13,34 and HPV negative tumors tend to be more treatment resistant. [10][11][12] Our analysis showed that 25% of the patients had HPV negative tumors, which was higher than previously reported. 35 This could be because our HPV assay did not specifically target the presence of E6/E7 mRNA, and that in situ hybridization was used without cross-testing with another HPV detection tool.…”
Section: Discussioncontrasting
confidence: 66%
“…Lymph node metastases have previously been shown to be a significant prognostic factor 13,34 and HPV negative tumors tend to be more treatment resistant. [10][11][12] Our analysis showed that 25% of the patients had HPV negative tumors, which was higher than previously reported. 35 This could be because our HPV assay did not specifically target the presence of E6/E7 mRNA, and that in situ hybridization was used without cross-testing with another HPV detection tool.…”
Section: Discussioncontrasting
confidence: 66%
“…The increased distant metastasis rate in those with an incomplete response after CRT may suggest this group with radioresistant disease is a different biological subgroup and continued interrogation of tumor biology is required. 37 Consistent with Bentzen et al, 35 a substantial proportion of those with residual tumor were not candidates for salvage surgery. Previous series have shown that a significant proportion of patients who have salvage surgery subsequently relapse and ultimately die of ASCC.…”
Section: Discussionmentioning
confidence: 56%
“…The prevalence of HPV in anal carcinoma is 88%, but has risen to 95% in studies using highly sensitive HPV detection methods . A better outcome of HPV‐positive AC, especially regarding loco‐regional response rates, has been reported . However, given the fact that most anal carcinomas are HPV positive, the mere detection of the viral genome is not sufficient for tumor stratification analyses, whereas identifying the factors and processes involved in HPV/host interactions that influence tumor cell behaviors is essential.…”
Section: Introductionmentioning
confidence: 99%
“…6 A better outcome of HPV-positive AC, especially regarding loco-regional response rates, has been reported. 7 However, given the fact that most anal carcinomas are HPV positive, the mere detection of the viral genome is not sufficient for tumor stratification analyses, whereas identifying the factors and processes involved in HPV/host interactions that influence tumor cell behaviors is essential. In particular, the change in the physical state of the viral genome in the host cell is a crucial step in the tumor process.…”
Section: Introductionmentioning
confidence: 99%